Prenatal Exposure to Δ9-Tetrahydrocannabinol Affects Hippocampus-Related Cognitive Functions in the Adolescent Rat Offspring: Focus on Specific Markers of Neuroplasticity - Valentina Castelli; Gianluca Lavanco; Salvatore Feo; Cesare D'Amico; Vincenzo Micale; Martin Kuchar; Fulvio Plescia; Anna Brancato; Carla Cannizzaro (MDPI AG, 2023)
Previous evidence suggests that prenatal exposure to THC (pTHC) derails the neurodevelopmental trajectories towards a vulnerable phenotype for impaired emotional regulation and limbic memory. Here we aimed to investigate pTHC effect on hippocampus-related cognitive functions and markers of neuroplasticity in adolescent male offspring. Wistar rats were exposed to THC (2 mg/kg) from gestational day 5 to 20 and tested for spatial memory, object recognition memory and reversal learning in the reinforce-motivated Can test and in the aversion-driven Barnes maze test; locomotor activity and exploration, anxiety-like behaviour, and response to natural reward were assessed in the open field, elevated plus maze, and sucrose preference tests, respectively. The gene expression levels of NMDA NR1-2A subunits, mGluR5, and their respective scaffold proteins PSD95 and Homer1, as well as CB1R and the neuromodulatory protein HINT1, were measured in the hippocampus. pTHC offspring exhibited deficits in spatial and object recognition memory and reversal learning, increased locomotor activity, increased NR1-, decreased NR2A- and PSD95-, increased mGluR5- and Homer1-, and augmented CB1R- and HINT1-hippocampal mRNA levels. Our data shows that pTHC is associated with specific impairment in spatial cognitive processing and effectors of hippocampal neuroplasticity and suggests novel targets for future pharmacological challenges.